Застосування генеративно-змагальних мереж при моделюванні плазмохімічних процесів отримання наносистем - Коротка, Лариса Іванівна; Макарченко, Віктор Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Для генерації додаткових даних при моделюванні плазмохімічних процесів отримання наносистем пропонується застосувати генеративно-змагальні мережі. Розглянуто проблемні аспекти процесу одержання таких навчальних даних, зокрема: якість синтетичних даних, збереження функціональних залежностей між вхідними та вихідними даними, стабільне навчання генератора та дискримінатора. Розібрано налаштування параметрів навчання нейронних мереж: значення шуму в генераторі, розмір латентного простору, функцій активації, відслідковування границь синтетичних даних після генерації. Спроєктовано та реалізовано відповідну архітектуру генеративно- змагальної мережі. Отримана синтетична вибірка використовується для навчання неглибоких нейронних мереж, а реальний набір даних використовується для перевірки якості навчання та тестування. The use of neural networks makes it possible to take into account the nonlinearity and complex relationships between the parameters of the technological process, which is multifactorial, with dependencies between the parameters that are difficult to formalize by classical methods. To generate additional data in modeling physiochemical processes for the production of nanosystems, it is proposed that generative adversarial networks (GANs) be used. The problematic aspects of the process of obtaining such training arrays are considered, in particular: the quality of synthetic data, preservation of functional dependencies between input and output data, and stable training of the generator and discriminator. The settings of neural network training parameters are analyzed: the value of noise in the generator, the size of the latent space, activation functions, and tracking the boundaries of synthetic data after generation. The necessity of adapting neural network approaches to the specifics of the process is substantiated. The search for the optimal architecture of the generative-adversarial network and parameter settings are considered. For example, a data augmentation strategy is required to train no-deep neural networks by generating synthetic data. It is proved that the lack of sufficient experimental data due to the high cost and complexity of conducting experiments can be compensated by fake generated data.
Application of generative-adversarial networks in modeling plasma-chemical processes for obtaining nanosystems
Keywords: генеративно-змагальні мережі; моделювання плазмохімічних процесів; отримання наносистем; синтетичні дані; навчання нейронних мереж; generative-adversarial networks; modeling of plasma-chemical processes; obtaining a nanosystem; synthetic data; training neural networks